Film Noir and the Folding of America: a Reading of Out of the Past (1947) and Impact (1949) - Childs, Jeffrey Scott (2020)
In his well-known work Le Plis: Leibniz et le baroque (1988), Gilles Deleuze proposes that the fold be understood as the central, “operative” concept of the Baroque, arguing that this figure allows us to grasp the seemingly paradoxical projection of space as differentiation-within-extension—i.e. as a continuous plane within which the fold itself produces both a dialectic of visibility and invisibility and radical juxtapositions. The relevance of this concept—and indeed of the Baroque in general—for the study of film noir has received scant attention, but it is precisely this figure that best articulates noir’s doubling of America into a region of shadows and hazy outlines, on one hand, and a land marked by clarity, transparency, and conspicuously marked boundaries. In this paper, I propose to establish the relevance of this concept for film noir through a comparative analysis of two of its manifestations: Jacques Tourneur’s Out of the Past (1947) and Arthur Lubin’s Impact (1949). The uncanny similarities between these two films—which tend to operate not on the level of plot but rather within the matrix of ideas that generate symbolic interest in the turns and outcomes of plot—suggest not a linear process of influence or homage but rather a convergence in the doubling of film noir’s relationship to its other space, its “other” America. Though referenced repeatedly in film noir, this other America is, in the films of Tourneur and Lubin, projected in concrete and overlapping forms, thus providing an occasion for an analysis of this space itself and of its relationship to the dominant space(s) of film noir.